Estudio del derecho de acceso a la slaud pública a personas con enfermedades catastróficas en la ciudad de Ibarra en el año 2023 - Perugachi Andrade, Franklin Joseph (2024)
The regulatory framework that regulates the right to the full exercise of the universal right to public health for people with chronic kidney diseases is quite broad, with an international and national framework that is sometimes far from the Ecuadorian reality, which allowed us to ask the following question research: How is the right of access to public health fulfilled for people with chronic kidney diseases in the city of Ibarra in the year 2023 and what factors influence its effectiveness?, leading to it being proposed as a general objective of This research analyzes the right of access to public health of people with chronic kidney diseases in the city of Ibarra in the year 2023, analyzing the regulatory framework and health policies, identifying the barriers in the Comprehensive Health Network and proposing recommendations to improve access to necessary medical care. Which led to the methodological application of a qualitative approach, with a level of descriptive depth, of the normativist, socio-legal, deductive and synthetic analytical method to ensure that Ecuadorian patients are informed about the right that applies to them. Without a doubt, the documentary review and interviews with experts in the area and kidney patients allowed us to have a broad and well-founded vision of the reality in terms of health in the city of Ibarra, which is characterized by facing certain barriers for people with chronic kidney diseases when accessing medical care through the Comprehensive Health Network\; However, the results credit the Ecuadorian State with ensuring and guaranteeing this right to free access to public health in its hospitals such as San Vicente de Paúl or through the intermediary network the Menydial Clinic, in cases of medical referrals.